Faktor-Faktor Yang Mempengaruhi Tax Avoidance Sektor Consumer Non-Cyclical di Bursa Efek Indonesia (2020–2024) - Handayani Z, Desi; Hayati, Triana Nurul; Rissi, Dita Maretha (Akuntansi dan Manajemen, 2025)
This study examines the effect of related party transaction, inventory intensity, fixed asset intensity, and independent commissioners on tax avoidance in consumer non-cyclical companies listed on the Indonesia Stock Exchange (IDX) during the 2020–2024 period, with firm size and leverage as control variables. Tax avoidance is measured using the Effective Tax Rate (ETR) as a proxy. The study employs a quantitative approach through multiple regression analysis using SPSS Statistics 31 and secondary data obtained from audited annual financial statements. The sample was determined using purposive sampling, resulting in 27 companies observed over five years. The results indicate that related party transaction and inventory intensity significantly affect tax avoidance, while fixed asset intensity and independent commissioners have no significant effect. Simultaneously, all independent variables together with firm size and leverage significantly influence tax avoidance. This study provides theoretical contributions to the accounting literature, particularly in taxation related to tax avoidance, and practical implications as a reference for stakeholders and policymakers in enhancing the effectiveness of tax regulations.